Cities, information, and the epigraphic habit: re-evaluating the links between the numbers of inscriptions and the sizes of sites - Hanson, JW (Brepols Publishers, 2021)
Among classical scholars there is a widespread assumption that there is no relationship between the sizes of communities and their epigraphic output. In this article, I offer a new model, which suggests two hypotheses for how inscriptions increase with population, depending on whether they can be regarded as a form of infrastructure or a measure of wealth or disposable income. I show that, despite the variation between sites, there is nonetheless a consistent relationship between the numbers of inscriptions and the estimated populations of sites. The numbers of inscriptions increase slower than the estimated populations of sites, however, suggesting that they acted as a form of information infrastructure. This has important implications for our understanding of the mechanisms for transmitting information in ancient contexts, suggesting several avenues for future research.